Selective-Tap Blind Dereverberation for Two-Microphone Enhancement of Reverberant Speech - Kokkinakis, Kostas (2009)
In this letter we propose a novel approach for two-microphone enhancement of speech corrupted by reverberation. Our approach steers computational resources to filter coefficients having the largest impact on the error surface and therefore only updates a subset of coefficients in every iteration. Experimental results carried out in a realistically reverberant setup indicate that the performance of the proposed algorithm is comparable to the performance of its full-update counterpart.